Carvedilol Combined With Ivabradine Improves Left Ventricular Diastolic Dysfunction, Clinical Progression, and Survival in Cirrhosis. Issue 6 (July 2020) - Premkumar, Madhumita; Rangegowda, Devaraja; Vyas, Tanmay; Khumuckham, Jelen S.; Shasthry, Saggere M.; Thomas, Sherin S.; Goyal, Ritu; Kumar, Guresh; Sarin, Shiv K.
Abstract : Background: Left ventricular diastolic dysfunction (LVDD) refers to impaired cardiac diastolic relaxation and may be improved by targeted heart rate reduction (THR). The authors evaluated whether a combination of carvedilol and ivabradine, an If channel blocker that reduces heart rate without affecting blood pressure, could improve LVDD and outcomes in cirrhosis. Patients and Methods: THR was defined as heart rate reduction to 55 to 65 beats per minute. Of 260 patients with cirrhosis, 189 (72%) with LVDD were randomized to THR [group (Gr.)A; n=94; carvedilol±ivabradine)] or standard care (Gr.B; n=95; no β-blockers) and followed for 12 months. Results: In Gr.A, THR was achieved at 4 weeks in 88 (93%) patients (responders, R): 48 (61.5%) with carvedilol alone and 40 (86.9%) of 46 patients with additional ivabradine. In Gr.A, LVDD reversed in 16 (20.5%) and improved from grade 2 to 1 in 34 (35.4%)], whereas in Gr.B, it progressed from grade 1 to 2 in 10 (10.5%) patients. At 12 months, 21 (11.1%) patients died, 6 (14%) in Gr.A and 15 (18%) in Gr.B ( P =0.240), but no mortality was seen in those who had persistent THR at 1 year (n=78; P =0.000). In multivariate analysis, model for end-stage liver disease [hazard ratio (HR), 1.52; 95% confidence interval (CI), 1.22-2.75; P =0.034] and E-wave transmitral/early diastolic mitral annular velocity (HR, 1.28; 95% CI, 1.23-2.42; P =0.048) predicted 1-year mortality. Nonresponders had an increased mortality risk (HR, 1.3; 95% CI, 1.2-1.8; P =0.046) independent of age, gender, and baseline model for end-stage liver disease. Levels of norepinephrine, N terminal brain natriuretic peptide, plasma renin activity, and aldosterone were reduced ( P <0.01) in responders. More patients in Gr.B developed acute kidney injury (odds ratio, 4.2; 95% CI, 2.8-10.5; P =0.027) and encephalopathy (odds ratio, 6.6; 95% CI, 1.9-9.7; P =0.040). Conclusions: Ivabradine combined with carvedilol improves LVDD, achieves THR more often and reduces risk of encephalopathy, acute kidney injury with improved survival in patients with cirrhosis. Abstract : Supplemental Digital Content is available in the text.